A Gas-Kinetic Scheme for Collisional Vlasov-Poisson Equations in Cylindrical Coordinates (Communications in Computational Physics, 2022)
Many configurations in plasma physics are axisymmetric, it will be moreconvenient to depict them in cylindrical coordinates compared with Cartesian coordinates. In this paper, a gas-kinetic scheme for collisional Vlasov-Poisson equations incylindrical coordinates is proposed, our algorithm is based on Strang splitting. Theequation is divided into two parts, one is the kinetic transport-collision part solved bymultiscale gas-kinetic scheme, and the other is the acceleration part solved by a Runge-Kutta solver. The asymptotic preserving property of whole algorithm is proved andit’s applied on the study of charge separation problem in plasma edge and 1D Z-pinchconfiguration. Numerical results show it can capture the process from non-equilibriumto equilibrium state by Coulomb collisions, and numerical accuracy is obtained.